High Stubble Height Enhances Ratoon Rice Yield by Optimizing Light–Temperature Resource Utilization and Photothermal Quotient - Yin Zhang; Tian Sheng; Liyan Shang; Beiyou Zhang; Long Jin; Fangfang Hou; Matthew Tom Harrison; Liying Huang; Zhaoqiang Jin; Xiaohai Tian; Ke Liu; Shijie Shi; et al. (Plants)
Ratoon rice is a sustainable planting model, and its yield is closely linked to the light and temperature use efficiency. The photothermal quotient (PQ), a key parameter for evaluating the light and temperature use efficiency, significantly influences ratoon rice yield. However, research on how different stubble heights affect PQ and the utilization efficiency of light and temperature resources remains limited. Here, we conducted a two-year field experiment to investigate the radiation use efficiency (RUE), effective accumulated temperature use efficiency (TUE), PQ, interception percentage (IP), intercepted photosynthetically active radiation (IPAR), and total dry weight (TDW) of six ratoon rice varieties under two stubble height treatments (HS: high stubble, LS: low stubble) during the ratoon season. This study aimed to analyze how different stubble heights impact ratoon rice yield by evaluating light and temperature resource utilization efficiency and investigates the relationship between PQ and ratoon rice yield. The results showed that the HS treatment significantly increased ratoon season yield compared to LS treatment, with average yield increases of 21.2% and 28.1% in 2022 and 2023, respectively. This yield enhancement was attributed to improved TDW under HS treatment, driven by increased IP, IPAR, RUE, and TUE. Notably, PQ was significantly lower under HS than under LS treatment. This reduction was primarily attributed to the decreased duration available for light and heat accumulation, consequently lowering PQ. Correlation analysis revealed a significant positive association between main season yield and PQ, while ratoon season yield exhibited a negative correlation with PQ. In conclusion, the HS treatment increased IP and IPAR, enhanced TUE and RUE, and reduced PQ, collectively contributing to higher ratoon season yields. Importantly, our findings indicate that PQ can more effectively predict yield changes in the ratoon season under HS treatment, providing a theoretical basis for optimizing light and temperature resource utilization in ratoon rice.